At the crossroad of unexplored paths: cultural back-translation and fantasy - Wüthrich, Julie (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
Cultural back-translation is the translation into language B of a text written in language A that takes its cultural basis from culture and language B. The peculiar translation trajectory involves a cultural return that differs from regular translations, as the audience will already be familiar with the work’s setting and cultural items. This implies a clear and familiar culture to return to: applying cultural back-translation to speculative fiction might sound implausible, as its subgenres are defined by important creative and invented components that more or less distort the real-life cultures they take inspiration from. As no research has been done on this yet, this paper seeks out and examines the existence of this phenomenon when applied to fantasy literature. After reviewing the terminology of the scattered research on cultural back-translation, this paper draws on multiple sources, from academic books to social media comments, to showcase the link between fantasy, translation, and cultural back-translation, then focuses on the analysis of Aliette De Bodard’s The House of Shattered Wings and an interview with its French translator Emmanuel Chastellière as a case study. It is argued here that as counterintuitive as it might seem, fantasy works can be analysed through the lenses of cultural back-translation and present a similar effect of familiarisation on the target audience, as well as an under-explored creative potential.
Keywords: Literary Translation